2010
DOI: 10.1016/j.npep.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of inducible and endothelial nitric oxide synthase by kinin B1 and B2 receptors

Abstract: Kinins are vasoactive peptides that play important roles in cardiovascular homeostasis, pain and inflammation. After release from their precursor kininogens, kinins or their C-terminal des-Arg metabolites activate two distinct G protein-coupled receptors (GPCR), called B2 (B2R) or B1 (B1R). The B2R is expressed constitutively with a wide tissue distribution. In contrast, the B1R is not expressed under normal conditions but is upregulated by tissue insult or inflammatory mediators. The B2R is considered to medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 144 publications
(209 reference statements)
1
92
2
5
Order By: Relevance
“…We found that B1R stimulation leads to G␣ i and ERK-mediated acute activation of inducible nitric-oxide synthase and prolonged high output NO production in human lung microvascular endothelial cells (17)(18)(19). Endotheliumspecific expression of B1Rs in transgenic rats increased hypotension and lethality in response to lipopolysaccharide (LPS) (20), whereas B1R knock-out protected mice from LPS-induced hypotension, reduced neuropathic pain, and pain in response to thermal or chemical stimuli (14).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We found that B1R stimulation leads to G␣ i and ERK-mediated acute activation of inducible nitric-oxide synthase and prolonged high output NO production in human lung microvascular endothelial cells (17)(18)(19). Endotheliumspecific expression of B1Rs in transgenic rats increased hypotension and lethality in response to lipopolysaccharide (LPS) (20), whereas B1R knock-out protected mice from LPS-induced hypotension, reduced neuropathic pain, and pain in response to thermal or chemical stimuli (14).…”
mentioning
confidence: 97%
“…B1Rs play important roles in the endothelium, for example by promoting angiogenesis (22) and stimulating nitric oxide production (17)(18)(19)64). Endothelial B1Rs can also have deleterious effects as shown by increased hypotension and lethality in response to lipopolysaccharide administration in transgenic rats with endothelium-specific overexpression of B1Rs (20).…”
mentioning
confidence: 99%
“…This view arose from work done in rodent cells, where iNOS expression can be induced to high levels and from the fact that iNOS has basal activity that is not dependent on increased [Ca 2ϩ ] i (3,19,56). Our study challenges this notion, as we find that eNOS can generate high output NO in human endothelium under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 72%
“…iNOS is considered to be the primary source of "high output" NO in inflammation (3,19,56). This view arose from work done in rodent cells, where iNOS expression can be induced to high levels and from the fact that iNOS has basal activity that is not dependent on increased [Ca 2ϩ ] i (3,19,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation